2012
DOI: 10.1097/scs.0b013e31824e6a44
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Management of Cerebrospinal Fluid Rhinorrhea

Abstract: The authors review their 5 years' experience with endonasal endoscopic repair of the anterior skull base fistulas presenting with cerebrospinal fluid (CSF) rhinorrhea. A total of 12 patients were managed endoscopically between 2004 and 2008. Seven patients (58.3%) had nonsurgical posttraumatic CSF rhinorrhea, 2 patients (16.7%) had CSF rhinorrhea due to surgical/iatrogenic trauma, and 3 patients (25%) had spontaneous onset of CSF rhinorrhea. Radiosurgical correlation for CSF fistula identification was positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 11 publications
1
28
0
1
Order By: Relevance
“…5 The most common sites of the leaks are the cribriform plate, ethmoid roof, and sphenoid sinus. 6,7 The incidence of iatrogenic CSF rhinorrhea has increased under the rapid development of skull base surgery. Endoscopic transsphenoidal surgery has been reported to have a 1.5% to 4.2% complication rate of CSF rhinorrhea depending on the surgeon's experience.…”
Section: Discussionmentioning
confidence: 99%
“…5 The most common sites of the leaks are the cribriform plate, ethmoid roof, and sphenoid sinus. 6,7 The incidence of iatrogenic CSF rhinorrhea has increased under the rapid development of skull base surgery. Endoscopic transsphenoidal surgery has been reported to have a 1.5% to 4.2% complication rate of CSF rhinorrhea depending on the surgeon's experience.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative medical treatment of CSF leaks includes absolute bed rest, antibiotics, putting a lumbar CSF drainage and administration of CSF production reducing drugs such as acetazolamide. 10 This treatment can lead to the development of spontaneous fibrosis, which in turn can help to achieve recovery in some cases. 10 However, the fibrosis-induced improvement before complete closure of the fistula defect still have risk of infection through the fistula region.…”
Section: Discussionmentioning
confidence: 99%
“…10 This treatment can lead to the development of spontaneous fibrosis, which in turn can help to achieve recovery in some cases. 10 However, the fibrosis-induced improvement before complete closure of the fistula defect still have risk of infection through the fistula region. 5,11 Conservative medical treatment also causes high hospital cost and more length of stay in the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approaches for surgical closure include intracranial, transnasal and combined. Endonasal endoscopic closure has become the preferred route for repairing cerebrospinal fluid leaks from anterior skull base as it avoids the need for a craniotomy and associated morbidity . A recent systematic review of endoscopic repair of cerebrospinal fluid leaks has shown a primary closure rate of 90% and low complication rates of <0.03% .…”
mentioning
confidence: 99%